Analisis Efektivitas Biaya Terapi Enoxaparin dan Fondaparinux Pada Pasien Jantung N-STEMI Rawat Inap di RSD K.R.M.T. Wongsonegoro - Purnami, Islina Dewi; Nugrahaeni, Atma Rulin Dewi; Khasanah, Ulfatun (Indonesian Journal of Medical and Pharmaceutical Science, 2023)
Background: N-STEMI heart disease in the community can provide a significant health and economic burden so that it can affect the quality of patient health. Enoxaparin and fondaparinux are often given to inpatients to overcome this problem because of the consideration between efficacy and safety of using drugs, one of which is the risk of patient bleeding. This study aim to determine the cost effectiveness of enoxaparin therapy and fondaparinux in the treatment of N-STEMI cardiac patients at RSD K.R.M.T. Wongsonegoro. Methods: This study is a descriptive observational method using a retrospective data collection from secondary data from the patient's medical record and the cost of care and treatment of patients during hospitalization. Processing of data in the form of numbers using Microsoft Excel then the data is processed according to the ACER and ICER calculation formulas. Results: The results show that compared to enoxaparin, fondaparinux is a cost-saving strategy (lower cost with slightly higher effectiveness). Fondaparinux is the most cost effective treatment for N-STEMI heart patients at RSD K.R.M.T. Wongsonegoro. Conclusion: Fondaparinux should be considered as a cost-effective alternative when compared to enoxaparin for inpatient N-STEMI cardiac patients at RSD K.R.M.T. Wongsonegoro based on length of hospitalization and duration of therapy, especially in the era of limited health resources.